Volumetric magnetic resonance-guided high-intensity focused ultrasound ablation of uterine fibroids through abdominal scars: the impact of a scar patch on therapeutic efficacy and adverse effects - Keserci, Bilgin (J Ther Ultrasound, 2017)
BACKGROUND: To retrospectively compare the treatment success, therapeutic efficacy, and adverse effects of magnetic resonance-guided high-intensity focused ultrasound (MRgHIFU) treatment for uterine fibroid patients with and without abdominal scars. METHODS: Seventy-six women who underwent treatment were divided into group 1 (patients with abdominal scars, which were covered with scar patches that prevents ultrasound energy from reaching the scar tissue immediately behind the patch) and group 2 (patients without abdominal scars). Non-perfused volume (NPV) ratios immediately after treatment, and fibroid volume reduction ratios and symptom severity scores (SSS) at the 6-months follow-up were assessed. All adverse effects were recorded. RESULTS: The mean NPV ratios in groups 1 and 2 were 87.0 ± 14.1% and 91.5 ± 13.3%. At the 6-months follow-up, the fibroid volume reduction ratios in groups 1 and 2 were 0.45 ± 0.27 and 0.43 ± 0.21, and the corresponding improvement in mean transformed SSS were 0.7 ± 0.39 and 0.79 ± 0.28, respectively. No serious adverse effects were reported. The minor adverse effects encountered in this study are likely related to the temperature increase in the near-field of the ultrasound beam path, which inevitably leads to skin burns, or far-field heat absorption by distant bony structures (i.e., sciatic nerve symptoms), and are typically manifested inter-procedurally and resolved shortly thereafter. CONCLUSIONS: The findings in this study suggest that the scar patch could be used safely and efficiently in MRgHIFU treatment for the patients with uterine fibroids and abdominal scars in the ultrasound beam path.